Case report: Rare among ultrarare—Clinical odyssey of a new patient with Ogden syndrome - Hofman, Jagoda; Hutny, Michal; Chwialkowska, Karolina; Korotko, Urszula; Loranc, Karolina; Kruk, Anna; Lechowicz, Urszula; Rozy, Adriana; Gajdanowicz, Pawel; Kwasniewski, Miroslaw; Krajewska-Walasek, Malgorzata; Paprocka, Justyna; et al. (Frontiers in Genetics, 2022)
Introduction: The definition of ultra-rare disease in terms of its prevalence varies between the sources, usually amounting to ca. 1 in 1.000.000 births. Nonetheless, there are even less frequent disorders, such as Ogden syndrome, which up to this day was diagnosed in less than 10 patients worldwide. They present typically with a variety of developmental defects, including postnatal growth retardation, psychomotor delay and hypotonia. This disorder is caused by the hetero- and homozygous mutations in NAA10 gene, which encodes N-alpha-acetyltransferase 10, involved in protein biosynthesis. Therefore, Ogden syndrome belongs to the broader group of genetic disorders, collectively described as NAA10-related syndrome. Case report: We present a case of a Polish male infant, born in 39. GW with c-section due to the pathological CTG signal. Hypotrophy (2400 g) and facial dysmorphism were noted in the physical examination. From the first minute, the child required mechanical ventilation - a nasal continuous positive airway pressure (nCPAP). For the first 27 days, the patient was treated in a neonatal intensive care unit, where a series of examinations were conducted. On their basis, the presence of the following defects was determined: muscular ventricular septal defects, patent foramen ovale, pectus excavatum, clubfoot and axial hypotonia. Child was then consequently referred to the genetic clinic for counselling. Results of the tests allowed the diagnosis of Ogden syndrome. In the following months the patient’s condition worsened due to the numerous pulmonary infections. Despite the advanced treatment including the variety of medications, the patient eventually died at the age of 10 months. Conclusion: This case report presents a tenth patient diagnosed with Ogden syndrome worldwide. It expands the morphologic and clinical phenotype, emphasizing the possible severity of pneumonological disorders in these patients, which may pose a greater threat to a child’s life than more frequently described cardiovascular dysfunctions associated with this syndrome.